Effect of Different Hormones Concentration on In vitro Regeneration of Apricot Cultivars - Muzaffer İpek; Şeyma Arıkan; Ahmet Eşitken; Servet Aras (Turkish Journal of Agriculture: Food Science and Technology)
The use of modern breeding methods along with appropriate cultivation techniques facilitates the acquisition and multiplication of varieties that possess the desired characteristics. Therefore, efforts towards the in vitro propagation of woody plants are increasing day by day. Today, plants such as Malus, Prunus, Pyrus, Ribes, Rubus, etc., can be successfully propagated in vitro. Apricot stands out as a stubborn species among Prunus types for shoot regeneration and genetic transformation. In this context, this study aims to determine how different plant growth regulators affect shoot regeneration of some native apricot varieties, which hold significant importance in apricot cultivation in our country. In the conducted study, mature cotyledons of Kabaaşı, Hacıhaliloğlu, and Hasanbey apricot varieties were used along with the culture medium consisting of MS. Different doses and ratios of plant growth regulators, including BAP and TDZ, in combination with NAA and GA3, were added to the culture media. At the end of the in vitro study, the callus and primordium formation rate (%), bud and shoot formation rate (%) and number of shoots per explant were recorded. According to the results, the variety with the highest callus formation was Kabaaşı, followed by Hasanbey and Hacıhaliloğlu. In all three varieties, the rate of callus formation decreased in media containing GA3. Regarding the stage of shoot regeneration from callus, the highest shoot formation with an average of 4 shoots per explant was observed in the Kabaaşı variety in the TDZ (1.0 mgL-1) + NAA (0.25 mgL-1) and TDZ (1.0 mgL-1) + NAA (0.50 mgL-1) media. Looking at the other varieties, the highest number of shoots, 1.6 shoots per explant, was obtained from the TDZ (2.0 mgL-1) + NAA (0.25 mgL-1) medium in Hasanbey and Hacıhaliloğlu varieties. As a result of the findings, the Kabaaşı variety showed the best result in terms of the regeneration capacity of apricot varieties. In contrast the best regeneration medium was obtained from the combinations of TDZ and NAA.